Synthesis and physical property characterization of nickel nanowires - Santhi, Ulakanathan (2021)
1D (one-dimensional) Ni (Nickel) NW (nanowire) is a metallic nanostructure that is anticipated to contribute substantially to material scientific advancement due to its unique chemical, mechanical, and magnetic properties. Hence, it is essential to ensure continuity of researches to utilize and optimize the exclusive properties of Ni NWs to develop high technology products. Therefore, the objectives of this research are as follows: to synthesize 1D Ni NWs using AAO (anodic aluminium oxide) template-assisted electrodeposition technique at various electrolyte bath temperatures and boric acid concentrations; to investigate the influence of electrolyte bath temperatures and boric acid concentrations towards physical properties of Ni NWs synthesized and to develop a mathematical equation using RSM (Response Surface Methodology) to correlate physical properties of Ni NWs towards synthesis condition. In this research, boric acid concentration was varied at 6, 40, and 70 g/L while the processing temperature was varied at 30, 70, and 110 °C. Physical properties of Ni NWs synthesized were analyzed using different characterization tools and both qualitative and quantitative findings were discussed in detail. Investigation using FESEM (Field Emission Scanning Electron Microscopy) showed the surface morphology became rougher with increasing electrolyte bath temperature and boric acid concentration. FESEM images also revealed that there is a growth in Ni NW length when the temperature increases but the NWs became shorter with high boric acid concentration. The elemental composition analysis using EDX (Energy Dispersive X-ray Detector) proved successful fabrication of high purity Ni NWs with 97.97 % Ni atom. XRD (X-ray Diffraction) finding showed the Ni NWs produced are in polycrystalline structure and the crystal orientation remains unchanged with different processing conditions. However, the crystal size became smaller with increasing boric acid concentration and grows bigger in a small percentage with higher deposition temperature. The mathematical equation was developed using RSM to corelate Ni NW growth length and crystal size towards the processing parameters employed in this research. The analysis showed that the temperature influences Ni NW growth length significantly, at 76.82 %. Meanwhile, the crystal size was influenced by boric acid concentration at 39.49% and electrodeposition bath temperature at 53.44 %. The error of experimental data versus predicted data for NWs growth length is 1.0 %, and for crystal size is 0.55 %. The established mathematical equation enables prediction of future values for specified processing conditions, thus eliminate the need to repeat the experiments and offers cost and time savings benefits.